Comparison of efficacy and side effects between short-course radiotherapy and chemotherapy with or without immunotherapy in the neoadjuvant treatment for patients with locally advanced rectal cancer - Niu, Shaoqing; Wen, Jie; Li, Yangchan; Yang, Jiayi; Xiong, Jianqi; Yang, Zhuangzhuang; Chen, Chuangqi; Yang, Yunying; Bao, Yong (Frontiers in Oncology, 2025)
PurposeTo evaluate the efficacy and safety of short-course radiotherapy (SCRT) combined with chemotherapy (ChT) with or without immunotherapy (IT) in the neoadjuvant treatment for patients with locally advanced rectal cancer (LARC).Materials and methodsClinicopathological data were retrospectively collected from LARC patients treated with SCRT combined with ChT with or without IT at our cancer center, from July 2021 to November 2024. The SCRT dose was 25 Gray (Gy), delivered daily for five consecutive days per week. The neo-ChT regimens included CapeOx and mFOLFOX. The IT regimen included cadonilimab, toripalimab, tislelizumab and sintilimab. The primary endpoint was the complete response rate after neoadjuvant treatment, including clinical complete response (cCR) and pathological complete response (pCR) rates. According to the treatment method, patients were divided into two groups: patients who received neoadjuvant SCRT and ChT with IT (SCRT+IT) group and who received neoadjuvant SCRT and ChT without IT (SCRT) group. The chi-square test was used to compare CR rates between groups, and logistic regression models were employed for univariate and multivariate analyses.ResultsFrom July 2021 to November 2024, of 50 LARC patients undergoing SCRT at our institution, 41 met the inclusion criteria: SCRT+IT group: (n=20) and SCRT group (n=21). Following neoadjuvant treatment, the SCRT+IT group achieved a complete response (CR) rate of 65.0% (13/20), comprising 9 pCR and 4 cCR. The SCRT group exhibited a pCR rate of 19.0% (4/21). This difference in CR rates was statistically significant (p = 0.003). Univariate and multivariate logistic regression analyses identified treatment modality (SCRT+IT vs. SCRT) as the sole independent predictor of CR (univariate: p = 0.003; multivariate: p = 0.017). The most common adverse reactions were grades 0 – 2, such as myelosuppression and radiation-induced rectal injury (RRI). 3 patients developed postoperative anastomotic leakage. In the SCRT+IT cohort, one patient experienced grade 3 immune-mediated hepatitis and one patient developed grade 3 immune-related pneumonitis.ConclusionCompared to SCRT combined with ChT alone, the combination of SCRT with ChT and IT significantly improves CR rate after neoadjuvant treatment, and the treatment-related adverse effects were tolerable.